Anaphylaxis with Schistosoma mansoni extracts in normal and infected mice - T. A. Mota-Santos; A. F. S. Oliveira; S. E. Gerken; N. M. Vaz (Revista do Instituto de Medicina Tropical de São Paulo, 1985)
Methods generally utilized for studies on anaphylaxis to protein antigens such as determination of histamine release to the blood, hemoconcentration, histamine release from peritoneal mast cells and passive cutaneous anaphylaxis (PCA) were used to investigate some aspects of the anaphylaxis to parasite antigens in Schistosoma mansoni infected mice. The release of histamine to the blood and significant rates of hemoconcentration were induced by intravenous injection of schistosomula or cercarial extracts into 10-13 weeks infected mice. Cercarial, schistosomula, worm tegument and soluble egg antigens were able to trigger histamine release from peritoneal mast cells from chronically infected mice. In spite of the PCA reaction beeing detected within 2 hours of sensitization (IgG1antibodies) in 6 of 8 tested sera from chronically infected mice, no detectable reactions were obtained after 48 hours sensitization (IgE antibodies). Although IgE was not detected in the circulation, by the PCA technique, the results indicate that the infected mice contained IgE antibodies bound to their mast cells.